Factors Affecting Earnings Management Practices in Mining Sector Companies on the Indonesian Stock Exchange 2018-2022 - Registiany, Via; Gomulia, Budiana; Setiawan, Amelia (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Earnings management is an interesting topic to discuss, considering that if you look at the facts in the field, there are still many companies that, in achieving their goals, tend to practice earnings management. Profit management practices often occur in various companies, one of which occurs in the mining sector, this is one of the problems in supporting the progress of the mining sector. This research aims to determine the factors that influence earnings management in mining sector companies on the Indonesia Stock Exchange 2018-2022. The research method used is the verification method. The population in this research is mining sector companies on the Indonesia Stock Exchange 2018-2022, totaling 44 companies. The sampling technique used was non-probability sampling with a purposive sampling method, so the sample was 25 companies. The data analysis used is panel data regression analysis using Eviews 13 software. The research results show that information asymmetry, managerial share ownership, profitability, and company age influence earnings management, while company size has no influence on earnings management. The magnitude of the influence of information asymmetry, managerial share ownership, profitability, company age and company size on earnings management is 56.55%.